The economic interests involved in the present war - Oldham, C.H. (Statistical and Social Inquiry Society of Ireland, 1915)
Adam Smith, in his final chapter, treats of Public Debts; he points out why the sudden and great expenditure on warfare is always met by borrowing instead of by increased taxation: "By means of borrowing," he says, "the governments are enabled, with a very moderate increase of taxes, to raise, from year to year, money sufficient for carrying on the war; and by the practice of perpetual funding, they are enabled, with the smallest possible in crease of taxes, to raise annually the largest possible sum of money." He proceeds to give his well-known argument that it would, in the long run, be much more economical to the community to meet war expenditure by taxes raised within the year rather than by funding. I do not now enter on that argument. War expenditure has always been met by borrowing, and during the continuance of the war the system of funding has great immediate advantages. It is only after the war - after the money has been expended - that we discover, when it is too late, the greater economy of the other system.
Read, Friday, April 30th, 1915
Keywords: War expenditure; World War One,; War, Economics; 314.15